Pengelolaan Teknologi Pendidikan dan Peranannya pada Pendidikan Agama Islam - Oga Sugianto; Mita Siti Afifah; Ni’matul Lathifah (Social Science Academic, 2023)
This study describes the management of educational technology and its role in Islamic religious education. The method used in this study uses a library research, that library research can be interpreted as a series of activities related to the methods of collecting library data, reading and recording and processing research materials. The results of this study indicate that with reason and the human mind is able to create a technology from a simple form, and is increasingly sophisticated as it is today. Thus providing convenience in every human activity. Technology has additional value in the learning process, this is because in the world of education the need for knowledge is increasing and not everything can be obtained in a school environment. Educational technology can only be developed and utilized properly if there are personnel who handle it. With the availability of educated and trained personnel in the field of Educational Technology, conceptually it will guarantee the effort to apply educational technology in institutions that organize learning. Furthermore, educational technology can only be recognized as a scientific discipline if it provides the possibility to conduct various kinds of research conducted with varied approaches according to the development of the research paradigm. The results of this study will support and strengthen learning technology as a scientific discipline that is not value-free in accordance with the concept of the Qur'an.